Cultural Significance of Jyapu Marriage Traditions - Shrestha, Meera Maiya (Nepalese Culture, 2026)
Among the various traditions performed in the Jyapu community, marriage tradition is a fundamental one. Specifically, in the life of a Jyapu woman, three distinct types of marriages are performed - Ihi, Bahra, and Ihipa. These marriages constitute various rituals, customs, and practices. However, there has been minimal academic research on the significance of these traditions, especially with an analysis towards its cultural implications. In this study, this gap has been substantially bridged by conducting a literature review- supported, interview-based ethnographic study. By conducting 62 field-based interviews and analyzing the responses, this study examines the rituals, customs, and practices of Jyapu marriages in depth and analyzes their cultural significance. For instance, it was identified that the Ihi and the Barha traditions allow a girl to understand the transitions in her body and her role in society. Similarly, the Ihipa or the actual marriage is the most significant tradition in a Jyapu community where not only two people are established in a union, but also their families are integrated. Furthermore, an interesting finding is the significance of gwe (betel nut) in Jyapu marriage, where it symbolically represents the transfer of responsibilities and the communication of decisions. Hence, through its presentation and analysis of the various rituals, customs, and practices of Jyapu marriage, this study contributes to the documentation, interpretation, and preservation of an important ritualistic aspect of Jyapu cultural heritage.